2017
DOI: 10.1038/s41598-017-16617-6
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of Breast Tumor by a Hand-held Impulse-Radar Detector: Performance Evaluation and Pilot Clinical Study

Abstract: In this report, a hand-held impulse-radar breast cancer detector is presented and the detectability of malignant breast tumors is demonstrated in the clinical test at Hiroshima University Hospital, Hiroshima, Japan. The core functional parts of the detector consist of 65-nm technology complementary metal-oxide-semiconductor (CMOS) integrated circuits covering the ultrawideband width from 3.1 to 10.6 GHz, which enable the generation and transmission of Gaussian monocycle pulse (GMP) with the pulse width of 160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 46 publications
0
66
0
Order By: Relevance
“…As Asian women have denser breast parenchyma than their European counterparts, these results will be essential in assessing the clinical utility of microwave imaging in dense breasts. Also, in 2017, a group from Hiroshima University, Japan, described early results of a handheld, radar-based system [73]. This study included five patients, all of whom had either IDC or DCIS.…”
Section: Microwave Breast Imaging (Mbi)mentioning
confidence: 99%
“…As Asian women have denser breast parenchyma than their European counterparts, these results will be essential in assessing the clinical utility of microwave imaging in dense breasts. Also, in 2017, a group from Hiroshima University, Japan, described early results of a handheld, radar-based system [73]. This study included five patients, all of whom had either IDC or DCIS.…”
Section: Microwave Breast Imaging (Mbi)mentioning
confidence: 99%
“…In the previous study, 43 the effect of EM wave on human body is investigated using the same antenna in simulation. It was found that with the same antenna, the calculated specific absorption rate (SAR) on the average mass of 1 g are from 0.0118 to 0.0246 W/kg across the UWB band.…”
Section: Realistic Phantommentioning
confidence: 99%
“…Examples are pre-hospital assessment, preventive screening, or long term monitoring following a medical procedure. MWI has been researched especially for stroke imaging [6], [7] and breast cancer imaging [8]- [10]. A different field in which radar and MWI techniques may prove successful, is monitoring of the cardiovascular system inside the body.…”
Section: Introductionmentioning
confidence: 99%